التقاضي الإلكتروني كآلية عصرية لمواجهة جائحة كورونا - زلومة, خديجة (جامعة الوادي.University eloued, 2022)
تماشيا مع التطور التكنولوجي لجأت وزارة العدل لعصرنة قطاع العدالة وذلك من خلال إصدار القانون 13/05، وفي أواخر 2019 وبعد ظهور جائحة كورونا التي أثرت سلبا على سير مرفق العدالة، كان لزامًا على الوزارة البحث على بدائل لضمان استمرارية هذا القطاع، ومن خلال المراسلة الصادرة عن السيد الأمين العام للوزارة في 15/03/2021 تحت رقم 302/ أع/2021 والتي تتضمن اعتماد آلية التقاضي الإلكتروني لغرض تبسيط الإجراءات القضائية وتسريعها، وتقديم خدمات للمتقاضين بشكل أفضل من القضاء التقليديAccording to the technological development, the Ministry of Justice resorted to modernizing the justice sector, through the issuance of Law 05/13, and in late 2019 and after the emergence of the Corona pandemic, which negatively affected the functioning of the justice facility, it was necessary for the Ministry to search for alternatives to ensure the continuity of this sector, and During the correspondence issued by Mr. Secretary General of the Ministry on 15/03/2021 under No. 302/SG/2021, which included the adoption of the electronic litigation mechanism to simplify and speed up judicial procedures, and providing better services than the traditional way.
م.س.اع22
Keywords: كوفيد-19؛ التقاضي الالكتروني؛ التكنولوجيا; Electronic Litigation; Covid-19; Technology